Production of Itraconazole Nanocrystal-Based Polymeric Film Formulations for Immediate Drug Release - Anna Karagianni; Leena Peltonen (MDPI AG, 2020)
In order to improve the solubility properties of BCS class II drug itraconazole, fast dissolving oral polymeric film formulations based on itraconazole nanocrystals were produced. Drug nanocrystals were manufactured by the wet pearl milling technique. In polymeric film formulations, hydroxypropyl methyl cellulose (HPMC) was used as a film forming polymer, and glycerin was used as a plasticizer. For nanocrystal suspensions and film formulations, thorough physicochemical characterization was performed, including particle sizing and size deviation, film appearance, weight variation, thickness, folding endurance, drug content uniformity, disintegration time, and dissolution profile. After milling, the nanoparticles were 369 nm in size with a PI value of 0.20. Nanoparticles were stable and after redispersion from film formulations, the particle size remained almost the same (330 nm and PI 0.16). The produced films were flexible, homogeneous, fast disintegrating, and drug release rate from both the nanosuspension and film formulations showed immediate release behavior. Based on the study, the film casting method for production of itraconazole nanocrystal based immediate release formulations is a good option for improved solubility.